Physicochemical, Nutritional, and Sensory Qualities of Wine Grape Pomace Fortified Baked Goods. Issue 9 (7th August 2014) - Walker, Rebecca; Tseng, Angela; Cavender, George; Ross, Andrew; Zhao, Yanyun
Abstract Wine grape pomace (WGP) as a source of antioxidant dietary fiber (DF) was used to fortify baked goods, including breads, muffins, and brownies. Pinot Noir WGP (RWGP) and Pinot Grigio WGP (WWGP) substituted wheat flour at concentration of 5%, 10%, and 15% for bread, 10%, 15%, 20%, and 25% RWGP for brownies, and 5%, 10%, and 15% RWGP or 10%, 15%, and 20% WWGP for muffins. The finished products were evaluated for total phenolic content (TPC), radical scavenging activity (RSA), and total DF, as well as physicochemical and sensory properties. WGP flour blends were also tested for solvent retention capacity (SRC). The highest TPC and RSA values for bread and muffins were achieved in 15% RWGP fortified samples with TPC and RSA values of 68.32 mg gallic acid equivalent (GAE)/serving and 80.70 AAE mg/serving, respectively for bread, and 2164 mg GAE/serving and 1526 mg AAE/serving, respectively for muffins. Brownies fortified with 10% RWGP had the highest RSA value (115.52 mg AAE/serving) while the control had the highest TPC value (1152 mg GAE/serving). Breads and muffins with 15% RWGP and brownies with 25% RWGP had the highest amount of DF (6.33, 12.32, and 7.73 g/serving, respectively). Sensory evaluation concluded that there is no difference in overall liking of 5% and 10% RWGP breads and muffins or 15% and 20% WGP brownies compared to the controls. This study demonstrated that WGP is a viable functional ingredient in bakery goods to increase TPC, RSA, and DF in consumer's diets.